The applications of data mining and machine learning in Bangladesh for disease pattern analysis and prediction - Mahmud, Mahmudul Hasan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.